Prevalence of severe malnutrition in cancer patients: a systematic review and meta-analysis - Hosseini, Sayed Mohsen; Salari, Nader; Darvishi, Niloofar; Siahkamari, Zahra; Rahmani, Adibeh; Shohaimi, Shamarina; Faghihi, Seyed Hassan; Mohammadi, Masoud (BioMed Central, 2025)
Background: Cancer remains the foremost cause of mortality worldwide. Additionally, malnutrition frequently occurs among cancer patients and constitutes a significant factor contributing to adverse clinical outcomes and poor prognosis in this population. The present systematic review and meta-analysis study aimed to evaluate the prevalence of severe malnutrition in cancer patients. Method: This study was conducted based on data extracted from previous published studies reporting the prevalence of malnutrition in cancer patients. Statistical analysis of collected data was performed using Comprehensive Meta-Analysis software (v.2). Systematic searching was applied based on MeSH keywords in medical databases of ScienceDirect, Embase, Scopus, PubMed, Web of Science (WoS), MagIran, SID, and Google Scholar (by December 2024). Following the elimination of duplicate articles, further evaluation was applied through the assessment of Titles and Abstract. Then, the eligibility assessment was performed based on the inclusion and exclusion criteria by two reviewers, independently. The information extracted from Citation Management Software of EndNote was also added. In order to achieve the highest number of eligible articles, the references of all relevant studies were reviewed, manually. Results: Totally, 19 eligible studies were selected for data extraction and meta-analysis. According to the Random Effect Model, the prevalence of severe malnutrition among cancer patients was reported 19.3% (95% CI: 14.1–25.9%). Also, the results of meta-regression examining the effective factors on heterogeneity, it was found that the rate of malnutrition in cancer patients decreases with sample size, year of study, and the age of cancer patients (p < 0.05). Conclusion: Malnutrition is a common phenomenon in cancer patients. Continuous monitoring of nutritional status in cancer patients and associated economic and social factors are critical objectives during cancer therapies. According to the results of the present study, cancer therapy should be applied parallel to examination and attention to nutritional status in cancer patients.